2016
DOI: 10.1016/j.clinph.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cortical correlates of response time slowing in older adults: ERP and ERD/ERS analyses during passive ankle movement

Abstract: ERP and ERD/ERS measurements during kinesthetic assessment provide new insights on identification of the origin of sensorimotor slowing in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 75 publications
7
31
2
Order By: Relevance
“…While the duration of ERPs is not longer than 600-800 ms, visual stimulation and working memory can induce changes in the alpha band oscillations lasting for 3 s (Chen et al, 2015). The differences in the duration of ERPs and ERD/ERS have been demonstrated in many studies with different kind of stimuli and tasks; in general ERD/ERS usually peak later than the ERP components (Anderson and Ding, 2011;Deiber et al, 2010;Toledo et al, 2016). In our study, ERD/ERS latencies were longer compared to the previously reported vMMN latencies; however, our results are in line with previous findings where oscillatory responses were late compared to ERPs.…”
Section: Erd/ers In Alpha Oscillationsmentioning
confidence: 99%
“…While the duration of ERPs is not longer than 600-800 ms, visual stimulation and working memory can induce changes in the alpha band oscillations lasting for 3 s (Chen et al, 2015). The differences in the duration of ERPs and ERD/ERS have been demonstrated in many studies with different kind of stimuli and tasks; in general ERD/ERS usually peak later than the ERP components (Anderson and Ding, 2011;Deiber et al, 2010;Toledo et al, 2016). In our study, ERD/ERS latencies were longer compared to the previously reported vMMN latencies; however, our results are in line with previous findings where oscillatory responses were late compared to ERPs.…”
Section: Erd/ers In Alpha Oscillationsmentioning
confidence: 99%
“…In the exercise of imagination, ipsilateral hemispheric μ rhythm and β rhythm are inhibited, while the countermeasures of halfbrain μ rhythm and β rhythm increases. This phenomenon is event-related desynchronization (ERD) or event-related synchronization (ERS) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related deterioration in the musculoskeletal and neuronal systems, in addition to reduced levels of selective attention and working memory, can lead to a decline of sensorimotor performance in older adults. Consequently, neuronal compensatory mechanisms such as activation of additional cortical areas [1][2][3] and increased cortical beta activity [4] are suggested to occur in older adults in an attempt to effectively perform specific tasks. Extra-activation could be understood as a functional reorganization and/or a redistribution of functional networks.…”
mentioning
confidence: 99%
“…Such information might provide meanings of how to prevent or revert functional sensorimotor deficits. A recent study from our laboratory combined electroencephalography (EEG) and response time (RT) task during brisk passive ankle movement and showed that worsening performance (longer RT) in older adults was correlated to delayed and weaker proprioceptive stimulus arrival at the cortex [4]. As a consequence, higher cognitive effort, suggested by larger eventrelated desynchronization (ERD) at beta band, was needed in order to process the reduced and time-dispersed peripheral input in aged individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation